2022
DOI: 10.1038/s41598-022-05111-3
|View full text |Cite
|
Sign up to set email alerts
|

Simulator acceleration and inverse design of fin field-effect transistors using machine learning

Abstract: The simulation and design of electronic devices such as transistors is vital for the semiconductor industry. Conventionally, a device is intuitively designed and simulated using model equations, which is a time-consuming and expensive process. However, recent machine learning approaches provide an unprecedented opportunity to improve these tasks by training the underlying relationships between the device design and the specifications derived from the extensively accumulated simulation data. This study implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…On one hand, the 2D materials could be an enabler for constructing devices for AI, such as memristors, photodetectors, etc. [118][119][120][121][122] . On the other hand, AI tools such as machine and deep learning can not only accelerate the discovery, design and optimization of 2D materials [123][124][125][126] , but also can interpret the signals generated by sensors based on 2D materials.…”
Section: The Meta-verse Of Composites Manufacturingmentioning
confidence: 99%
“…On one hand, the 2D materials could be an enabler for constructing devices for AI, such as memristors, photodetectors, etc. [118][119][120][121][122] . On the other hand, AI tools such as machine and deep learning can not only accelerate the discovery, design and optimization of 2D materials [123][124][125][126] , but also can interpret the signals generated by sensors based on 2D materials.…”
Section: The Meta-verse Of Composites Manufacturingmentioning
confidence: 99%
“…Deep and machine learning, which have been rapidly evolving recently, are being used in various fields such as image and natural language processing to effectively identify the relationship between complex input and output. Additionally, machine learning has broadened its application to address issues with the current device module simulator 4 7 . Recent studies have shown that advances in machine learning models, such as deep neural networks, mostly focus on solutions for partial differential equations, such as Maxwell’s equations for calculating electromagnetic values 8 13 and there are few studies on grid-wise techniques.…”
Section: Introductionmentioning
confidence: 99%
“…This study proposes a novel solution to the problem using a deep-learning method called inverse covariance estimating generative adversarial network (ICEGAN). Numerous studies have sought to apply deep learning to various problems [15][16][17][18] because of recent advancements in deep learning models. Consequently, effective applications in image classification [19,20], object detection [21,22], a variety of natural language processing challenges, including language translation [23,24] and text generation [25,26], and financial portfolio management [27] have been developed.…”
Section: Introductionmentioning
confidence: 99%